Evaluation of Drug Management at the Pharmacy Installation of "X" Regency Health Office Indonesian in 2021 - Naha Ndjurumbaha, Echa Malinda; Gunawan Pamudji Widodo; Ismi Rahmawati (Open Access Indonesian Journal of Medical Reviews, 2023)
Improving public health status can be influenced by the drug management process, one of the components of which is the availability of good drugs. This study aimed to find out the overall process description of drug management, which includes the planning, procurement, storage, and distribution stages, as well as to know the evaluation of drug management related to compliance with the indicators of the Ministry of Health of the Republic of Indonesia & JICA 2010. This study used a type of research descriptive data collection with retrospective and concurrent. Data analysis was carried out by explaining the drug management process at the "X" Regency Health Office, measuring the value of each drug management indicator, and then making a problem-solving based on the Hanlon method. The results of the evaluation of drug management at the Pharmacy Installation of the "X" Regency Health Office were the suitability of the available drug items with the Fornas of 54%; percentage of fund allocation procurement drugs by 93%; percentage suitability of drug planning and procurement by 73%; the percentage of drug planning accuracy is 84%; percentage and value of expired drugs by 8% worth Rp. 39,888,756; The accuracy of drug distribution is 94%; drug availability12-18 months of 94%; and the percentage of drug blanks is 2%. Some indicators are not up to standard, so improvements are made using the Hanlon method.